Evaluation of twin-arginine translocation substrate proteins as potential antigen candidates for serodiagnosis of brucellosis - Yao Wu; Yao Wu; Xin Yan; Mingjun Sun; Xiaohan Guo; Jiaqi Li; Xiangxiang Sun; Xiangxiang Sun; Mengda Liu; Mengda Liu; Haobo Zhang; Haobo Zhang; et al. (Frontiers in Veterinary Science)
IntroductionBrucellosis, an infectious zoonotic disease caused by members of the genus Brucella, results in chronic multi-organ injury. Improving the specificity and sensitivity of serological methods for diagnosing brucellosis necessitates the development of novel diagnostic antigens. The twin-arginine translocation (Tat) pathway is responsible for transporting folded proteins across the cytoplasmic membrane and has been implicated in the virulence of Brucella. Three Tat substrate proteins—L,D-transpeptidase ErfK (A0577), linear amide C-N hydrolase YxeI (A1479), and thioesterase domain-containing protein EntF (B0249)—contribute significantly to Brucella virulence. However, the roles of these Tat substrate proteins in diagnosing brucellosis remain unclear.MethodsIn this study, ErfK, YxeI, and EntF were expressed in prokaryotic cells and utilized as diagnostic antigens. The clinical sera from bovines and sheep diagnosed with brucellosis were analyzed using indirect ELISA with these proteins.ResultsFor bovine serum, the combined protein group (ErfK + YxeI + EntF) and YxeI demonstrated the highest diagnostic accuracy of 94.23% and 93.58%, respectively. Meanwhile, the combined protein group showed the strongest ability to detect Brucella in sheep serum, achieving an accuracy of 88.10%. Both the combined protein group and YxeI displayed no cross-reactivity with rabbit serum immunized against Yersinia enterocolitica O9, Escherichia coli O157:H7, Mycobacterium tuberculosis, Vibrio cholerae, Legionella, and Salmonella, indicating relatively good specificity.ConclusionThe findings of this study suggest that Tat substrate proteins serve as promising candidate antigens with significant potential value for the clinical diagnosis of brucellosis.